Hybrid Project Management : A Qualitative Inquiry into Adoption and Implementation in Organizations - Krupa, Miroslav; Mládková, Ludmila, 1963-; Dvouletý, Ondřej; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Hybrid Project Management (HPM) has emerged as a project management approach that combines elements of traditional and agile methodologies to leverage the advantages and suppress the disadvantages of both, aiming to increase project success. This approach balances flexibility, effectiveness, productivity, and control, making it suitable for various project contexts. Despite the increasing prevalence of HPM, there is a limited understanding of the motivations behind its adoption, the challenges organizations face during its implementation and its practical application. This dissertation addresses these gaps by establishing a strong theoretical foundation through a systematic literature review, which anchored HPM within the project management field, mapped its advantages, disadvantages, drivers, and barriers, and provided a comprehensive overview of existing HPM models. The dissertation conducted a qualitative inquiry involving nine case studies, supported by 36 semi-structured interviews, 24 observations, and 15 organizational documents, to explore the factors driving the adoption of HPM, the strategies organizations employ for its implementation, and the execution dynamics in different organizational environments. The findings reveal that HPM adoption is primarily driven by the need to manage increasing project complexity, where neither traditional nor agile methodologies alone are sufficient to address its demands. However, the implementation strategies are heavily influenced by the organizational context, with two primary adoption pathways, conscious and unconscious, emerging from the data. Notably, the study identifies instances of unconscious HPM adoption, a phenomenon not previously analyzed in project management studies. Furthermore, a gradual, incremental implementation and continuous improvement approach was observed across all cases, suggesting that HPM is not a one-off change but an ongoing adaptation process.
This research contributes to the project management field by proposing an HPM adoption model that accounts for varied organizational contexts and highlights the adaptive and context-dependent nature of HPM adoption. The model offers practical insights for organizations aiming to enhance their project management practices through a structured yet flexible approach that accommodates both strategic goals and the dynamic requirements of complex projects.
Vedoucí práce: Ludmila Mládková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management a manažerská ekonomie [obor disert. práce]; disertace; dissertations